Effect and factors associated with reactivation after intravitreal conbercept or aflibercept in retinopathy of prematurity - Chunling Huang; Weikang Zou; Wenbei Ma; Jiali Li; Yichen Bai; Rong Wu; Qiqi Li; Qi Fang; Wenna Chen; Xiaohe Lu; Songfu Feng (European Journal of Medical Research)
Abstract Background To evaluate the effect and factors associated with the reactivation of retinopathy of prematurity (ROP) after intravitreal conbercept or aflibercept. Methods We retrospectively reviewed the medical records of 176 eyes diagnosed with ROP and treated with anti-VEGF therapy between January 2018 and September 2022. The rate of reactivation and complications were assessed during the follow-up period. The factors of reactivation of ROP after intravitreal conbercept or aflibercept were analyzed on the basis of clinical factors and retinal parameters. Results Reactivation of ROP occurred in 10 eyes (13.9%) after intravitreal conbercept and 13 eyes (12.5%) after intravitreal aflibercept (P = 0.79). The interval between injection and reactivation was significantly longer in the aflibercept group than in the conbercept group (15.50 ± 4.05 vs. 5.36 ± 0.50 weeks) (P < 0.001). The central retinal arteriolar equivalent (CRAE) of aggressive ROP was larger than that of type 1 prethreshold and threshold ROP before anti-VEGF therapy (P < 0.05). Zone I and stage 3 exhibited a positive correlation with the reactivation of retinopathy of prematurity (ROP) [odds ratio (OR) = 20.15, 5.02]. The changes in CRAE of pre-and post-therapy and gestational age were identified as potential protective factors for these outcomes (OR = 0.23, 0.49). Conclusions Conbercept and aflibercept are effective for treating ROP. Aflibercept resulted in longer treatment intervals compared to conbercept. Zone, stage, and gestational age were associated with the reactivation of ROP. CRAE was associated with not only the severity of ROP but also its reactivation. Additionally, it may be an objective indicator in the early indication and follow-up of ROP.